The earthworm—Verminephrobacter symbiosis: an emerging experimental system to study extracellular symbiosis - Lund, Marie B.; Kjeldsen, Kasper U.; Schramm, Andreas (Frontiers in Microbiology, 2014)
Almost all Lumbricid earthworms (Oligochaeta: Lumbricidae) harbor extracellular species-specific bacterial symbionts of the genus Verminephrobacter (Betaproteobacteria) in their nephridia. The symbionts have a beneficial effect on host reproduction and likely live on their host’s waste products. They are vertically transmitted and presumably associated with earthworms already at the origin of Lumbricidae 62 – 136 million years ago. The Verminephrobacter genomes carry signs of bottleneck-induced genetic drift, such as accelerated evolutionary rates, low codon usage bias, and extensive genome shuffling, which are characteristic of vertically transmitted intracellular symbionts. However, the Verminephrobacter genomes lack AT bias, size reduction, and pseudogenization, which are also common genomic hallmarks of vertically transmitted, intracellular symbionts. We propose that the opportunity for genetic mixing during part of the host – symbiont life cycle is the key to evade drift-induced genome erosion. Furthermore, we suggest the earthworm-Verminephrobacter association as new experimental system for investigating host-microbe interactions, and especially for understanding genome evolution of vertically transmitted symbionts in the presence of genetic mixing.